PENGARUH LITERASI KEUANGAN, LOCUS OF CONTROL DAN PENDAPATAN TERHADAP KEPUTUSAN INVESTASI MAHASISWA UNIVERSITAS MAHASARASWATI DENPASAR - Dewi , Ni Luh Putu Cahya; Astiti, Ni Putu Yeni; Mentari, Ni Made Indah (JUIMA : JURNAL ILMU MANAJEMEN, 2025)
Investment activities are a model of fund allocation that is quite promising for the future. In the selection of investment decisions made by investors, it can be influenced by both rational and irrational factors, such as knowledge, information obtained by the investor, and psychological factors. A higher level of financial literacy can lead to better investment choices and help investors avoid losses. Investment decisions and locus of control are two principles that are interconnected in psychology and economics; the better the locus of control possessed by the investor, the better the investment decisions made. A high income will make it easier for investors to meet their needs and goals, and some can be set aside for investment. This study aims to explain the influence of financial literacy, locus of control, and income on the investment decisions of students at Universitas Mahasaraswati Denpasar. The population of this study consists of students from the Capital Market Studies program at Universitas Mahasaraswati Denpasar. The sample in this study consisted of 92 respondents who were selected using the census technique or saturated sampling. The analysis technique applied in this study is multiple linear regression analysis. The findings of this study indicate that financial literacy, locus of control, and income each have a positive impact on the investment decisions of students at Universitas Mahasaraswati Denpasar.